Antioxidants-rich ice cream containing herbal extracts and fructooligossaccharides: manufacture, functional and sensory properties. (15th November 2019) - Gremski, Leonardo Augusto; Coelho, Ana Letícia Kincheski; Santos, Jânio Sousa; Daguer, Heitor; Molognoni, Luciano; do Prado-Silva, Leonardo; Sant'Ana, Anderson S.; da Silva Rocha, Ramon; da Silva, Márcia Cristina; Cruz, Adriano Gomes; Azevedo, Luciana; do Carmo, Mariana Araújo Vieira; et al.
Graphical abstract: Highlights: A mixture of I. paraguariensis, M. officinalis, and C. citratus was optimized. The optimized extract (OHE) had antioxidant, antihypertensive and antiproliferative activity. OHE decreased ROS generation in IMR90 and A549 cell lines. OHE is rich in rutin, isoquercetin, and hesperidin. OHE promoted in vitro antihypertensive properties and increased phenolics/antioxidant activity. Abstract: This work aimed to optimize an aqueous extract rich in phenolic compounds and potential functional properties made of Ilex paraguariensis, Melissa officinalis, and Cymbopogon citratus. The lyophilized extract was used for the development of an ice cream. Total phenolics, FRAP, DPPH, Folin-Ciocalteu's reducing capacity, and total reducing capacity of different combinations of herbal extracts were tested and modeled using response surface methodology. Simultaneous optimisation was employed to maximize the bioactive compounds in the extract and the lyophilized optimum combination was added to ice cream. The lyophilized extract contained quercetin-3-rutinoside, hesperidin, isoquercetin, caffeic acid, and 5, 7-dihydroxyflavone. The optimised extract, which showed antihypertensive, antidiabetic, and antioxidant activity using in vitro protocols, increased total phenolics and antioxidant activity in comparison to the control ice cream. The ice cream presented a sensory acceptance index of 83%. After 72 days of storage (−18 °C), total phenolics and antioxidant activity significantly decreased.